A Survey of Retinal Remodeling - Strettoi, Enrica (Frontiers in Cellular Neuroscience, 2015)
Up to 15 years ago, bibliographic searches based on keywords such as “photoreceptor degeneration, inner retina” or “photoreceptor degeneration, second order neurons” returned only a handful of papers, as the field was dominated by the general assumption that retinal degeneration had direct effects on the sole populations of rods and cones. Since then, a number of studies have been dedicated to understanding the process of gradual morphological, molecular, and functional changes arising among cells located in the inner retina (comprising neurons, glia, and blood vessels), that is to say “beyond” photoreceptors. General aspects of this progression of biological rearrangements, now referred to as “remodeling”, were revealed and demonstrated to accompany consistently photoreceptor loss, independently from the underlying cause of degeneration. Recurrent features of remodeling are summarized here, to provide a general frame for to the various analytical descriptions and reviews contributed by the articles in the issue (among others, see Euler and Schubert, 2015; Soto and Kerschensteiner, 2015, this issue).